Efficient Beamforming by SLNR Maximization for Dual-Hop Relay Assisted MIMO Network - Saand, A.S. (Springer New York LLC, 2016)
Relay beamforming is a key signal processing technique to mitigate interference in single and multiuser multiple input and multiple output (MIMO) wireless communication networks. In MIMO relay networks interference cancellation is an essential task of the study to get optimal network capacity. In this paper, the problem of interference resulted from leakage signal from desired signal for intended antenna, which causing interference to other antennas of the same user with multiple antennas is tackled. The criterion of signal to leakage plus noise ratio (SLNR) maximization is considered to design a vector by vector relay downlink precoding based on Fukunaga Koontz transform. This can control the interference among multiple antennas and maximize SLNR. However, matched filter beamforming is utilized at the relay receiving side that can increase output signal to noise ratio at the relay node. The channel state information of both the channel between source to relay and relay to destination is assumed at the relay node. The effectiveness of the proposed technique is studied and compared with conventional relay precoding techniques. Simulation is carried out in MATLAB environment using ideal channel conditions. This study demonstrates that, the proposed scheme for relay assisted MIMO networks can improve overall system performance in terms of ergodic capacity. Â© 2015, Springer Science+Business Media New York.